Development of EMG based Upper Arm Exoskeleton - Ying, G.L. (Institute of Electrical and Electronics Engineers Inc., 2019)
This research paper presents the study on design of arm exoskeleton for stroke rehabilitation purpose. The mechanical design of the exoskeleton focuses on few aspects of the arm exoskeleton which are length and the design of the exoskeleton and motor specification. Besides, the experiment of obtaining surface electromyography (sEMG) signal for repetition training for physiotherapy patient purpose is carried out to observe the difference in amplitude and muscle signal of different subjects (four males and four females) due to the amount of training and the angle of the training. The signals are filtered and the average of the root mean square of the data is compared. Â© 2018 IEEE.